MYC: Master Regulator of Immune Privilege. Issue 4 (April 2017) - Casey, Stephanie C.; Baylot, Virginie; Felsher, Dean W.
Abstract : Cancers are often initiated by genetic events that activate proto-oncogenes or inactivate tumor-suppressor genes. These events are also crucial for sustained tumor cell proliferation and survival, a phenomenon described as oncogene addiction. In addition to this cell-intrinsic role, recent evidence indicates that oncogenes also directly regulate immune responses, leading to immunosuppression. Expression of many oncogenes or loss of tumor suppressors induces the expression of immune checkpoints that regulate the immune response, such as PD-L1. We discuss here how oncogenes, and in particular MYC, suppress immune surveillance, and how oncogene-targeted therapies may restore the immune response against tumors. Trends: Oncogenes such as MYC may drive tumor growth not only through their intrinsic influence on cellular proliferation but also through their regulation of immune checkpoints that enables evasion from immune surveillance. The MYC oncogene causally regulates immune checkpoint expression. Other oncogene proteins including EGFR, STAT3, BRAF, β-catenin, and AKT/mTOR, as well as loss of tumor-suppressor genes such as PTEN, appear to regulate PD-L1 expression. Targeted inactivation of an oncogene with therapy may restore an immune response against tumors and remodel the tumor microenvironment.